2016
DOI: 10.1080/02827581.2016.1220618
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between TanDEM-X- and ALS-based estimation of aboveground biomass and tree height in boreal forests

Abstract: Interferometric Synthetic Aperture Radar (InSAR) data from TanDEM-X were used to estimate above ground biomass (AGB) and tree height with linear regression models.These were compared to models based on airborne laser scanning (ALS) data at two Swedish boreal forest test sites, Krycklan (64°N19°E) and Remningstorp (58°N13°E).The predictions were validated using field data at stand-level (0.5 ha -26.1 ha) and at plot-level (10 m radius). Additionally, the ALS metrics percentile 99 and vegetation ratio, commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 44 publications
4
42
0
Order By: Relevance
“…With the overall better correspondence with the field plot data (lower standard error) and decreased variance as the larger radii were evaluated, it was determined that a 40 m radius was more robust to use, despite the smaller sample radius. This also agrees with the findings in [16].…”
Section: Data Extractionsupporting
confidence: 83%
See 2 more Smart Citations
“…With the overall better correspondence with the field plot data (lower standard error) and decreased variance as the larger radii were evaluated, it was determined that a 40 m radius was more robust to use, despite the smaller sample radius. This also agrees with the findings in [16].…”
Section: Data Extractionsupporting
confidence: 83%
“…The residual phase trend is caused by small errors in the satellite positions, which result in baseline errors. Similar trends have been reported by other authors [6,15,16,21,49]. The error is easily observed in overlapping areas between adjacent swaths and can be corrected, to first order, by fitting an error model to the data.…”
Section: Scenes With Phase Trendssupporting
confidence: 68%
See 1 more Smart Citation
“…From the scatter plots it can be concluded that estimations at higher volume/biomass possess considerably higher standard deviations, which might indicate a limited applicability for denser forest and southern forests with higher volumes/biomasses. Experience from using field data from these test sites together with other sensors (for example TanDEM-X radar data [36]) has shown that the standard deviations can remain constant along the entire evaluated range. In the current study, the heights generally had to be transformed to achieve significance in the regression modelling, and in Krycklan the heights were raised to the power of 2.3 while at Remningstorp the height was raised to the power of 2.6 and 2.7 for VOL and AGB, respectively (Tables 6 and 7).…”
Section: Discussionmentioning
confidence: 99%
“…These factors, as well as information on the elevation of the ground, need to be considered when estimating biomass from the InSAR height. Several research papers demonstrated that simple linear relationships could predict biomass from estimates of InSAR height of single-pass datasets [35][36][37][38][39][40][41][42]. Nevertheless, it is unclear whether such linear models that were validated at a number of test sites in boreal and savannah forest apply in other forest ecosystems as well [42].…”
Section: Retrieval Of Biomass Using Insar Observationsmentioning
confidence: 99%